IEEE International Magnetics Conference 1999
DOI: 10.1109/intmag.1999.837855
|View full text |Cite
|
Sign up to set email alerts
|

La-Co substitutedSr ferrite magnets

Abstract: SnbductionAlthough the magnetic properties of commercial SI femte magnets have been impmved mainly by means of process optimization, the further improvement is intensively demanded in automobile and electric appliance industry. In this study, the effect of the partial substitution of F@+ and Srz+ ion for Cd' and Last ion respectively on the coerdve force of Sr ferrite magnets was investigated. The composition formula of ferrite materials which were investigated is as follows.(S++l.Laa+x)O * n((FeJ+~.yCo*+y)zOo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…M-type strontium hexaferrite (SrFe 12 O 19 ) has appropriate magnetic properties, chemical stability, and low cost compared with rare-earth compounds, it has attracted extensive interests in the past decades [1][2][3]. And in about year 2000 it had been reported that the magnetic performance of anisotropic M-type SrFe 12 O 19 hexagonal ferrites can be improved by applying La-Co substitution [4][5][6]. The obtained increase in both remanence and magnetic anisotropy is of particular importance [7].…”
Section: Introductionmentioning
confidence: 99%
“…M-type strontium hexaferrite (SrFe 12 O 19 ) has appropriate magnetic properties, chemical stability, and low cost compared with rare-earth compounds, it has attracted extensive interests in the past decades [1][2][3]. And in about year 2000 it had been reported that the magnetic performance of anisotropic M-type SrFe 12 O 19 hexagonal ferrites can be improved by applying La-Co substitution [4][5][6]. The obtained increase in both remanence and magnetic anisotropy is of particular importance [7].…”
Section: Introductionmentioning
confidence: 99%